PENGARUH WAKTU INSEMINASI TERHADAP MOTILITAS DAN VIABILITAS SPERMATOZOA PASCAINSEMINASI PADA KAMBING - Indah Norma Triana (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
The purpose of this research was to know the effect of insemination time on motility and viability of spermatozoa in egg yolk tris diluter post insemination of goat. In this research 20 female goats was used and divided into two groups and synchronized with PGF2 alfa. If sign of oestrus appeared, then goats in group I, were inseminated with semen from buck diluted with egg yolk tris at the beginning of oestrus and group II inseminated with semen from buck diluted with egg yolk tris at the mid oestrus. Semen was collected from cervical canal of goats at one, two, 3, 6, or 24 hours after insemination for evaluating its motility and viability. Implication of this research is indicate that artificial insemination can be conducted in the early also the mid oestrus of goat.